Population and Modeling of Transportation Process - Horváth, R. (Acta Technica Jaurinensis, 2011)
Different types of models have been in use for decades in order to describe transportation networks. These models make it possible to portray real systems using qualitative and quantitative parameters, therefore they can be examined. Conventional transportation simulation models are difficult to use in the case of complex systems as well as not or simply restrictedly containing data, which are necessary to describe the system. Urban transportation systems are often complex with many different types of parameters and their relationships. In certain cases, these systems can easily be described by system dynamics tools. This article introduces a cooperation of a system dynamics model and conventional transport planning system.